The Impact of Phaleria macrocarpa Fruit Flavonoid Extract on Endometrial Thickness in Mice Menopausal Model - Wijaya, Dyah Ayu Septika; Dwi Wulandari, Recavery; Sutrisno, Sutrisno; Irwanto, Yahya; Anita, Kenty Wantri (Medical Laboratory Technology Journal, 2024)
This study aims to determine how the effect of flavonoid phaleria macrocarpa fruit extract on the endometrial thickness of Mus musculus which is used as an experimental animal with a menopause model. This study employed a randomized post-test-only control group design on 32 female mice. Ovariectomy simulated menopause, followed by treatment with flavonoid from Phaleria macrocarpa fruit extract. Post-observariectomized, follicle-stimulating hormone levels indicated menopausal status. Hematoxylin-Eosin methods assessed endometrial thickness. The result indicated reduced endometrial thinning in the positive control group (K+). Conversely, the treatment group (P1-P4) exhibited increased endometrial thickness post-flavonoid extract administration. Ovariectomized-induced estrogen decline resulted in reduced endometrial thinning, mimicking menopausal conditions. Statistically, flavonoid extract administration increased endometrial thickness in ovariectomized-induced menopausal mice, with optimal effect observed at 7.5 mg/mice/day for 14 days. The preferred intervention dose for altering endometrial thickness in menopausal conditions was identified as P1 (3.75 mg/mice/day). In conclusion, a flavonoid from Phaleria macrocarpa fruit extract mitigates endometrial thinning in the menopausal mice model. For implication in menopausal women, clinical trials need to be conducted to evaluate the dosage of these flavonoids for their potential as a natural SERM (Selective Estrogen Receptor Modulator) before clinical application in managing endometrial health. Additionally, research on molecular effects particularly regarding ER (Estrogen Receptors) in the endometrial organ, is needed to confirm their phytoestrogenic effect.